2019
DOI: 10.1186/s13046-019-1439-x
|View full text |Cite|
|
Sign up to set email alerts
|

JMJD2C promotes colorectal cancer metastasis via regulating histone methylation of MALAT1 promoter and enhancing β-catenin signaling pathway

Abstract: BackgroundOur previous work demonstrated that lncRNA-MALAT1 was overexpressed in recurrent colorectal cancer (CRC) and metastatic sites in post-surgical patients. However, the upstream regulatory mechanism of MALAT1 is not well-defined. Histone demethylase JMJD2C holds great potential of epigenetic regulating mechanism in tumor diseases, especially the moderating effect on the promoter activity of targeted genes associated closely with tumor development. Therefore, we herein investigated whether JMJD2C could e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…To date, numerous studies have demonstrated a crucial role for both hypermethylation of tumor suppressor genes and hypomethylation of oncogenes in cancer development and progression [30]. For example, Wu et al [32] found that JMJD2C could enhance the metastasis of colorectal cancer by decreasing the histone methylation of the MALAT1 promoter, thereby upregulating MALAT1 expression and enhancing the activity of the β-catenin signaling pathway. Furthermore, Liang et al [33] identified many novel methylation-regulated differentially expressed genes involved in colon cancer tumorigenesis and progression by identifying hypermethylated downregulated genes and hypomethylated upregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies have demonstrated a crucial role for both hypermethylation of tumor suppressor genes and hypomethylation of oncogenes in cancer development and progression [30]. For example, Wu et al [32] found that JMJD2C could enhance the metastasis of colorectal cancer by decreasing the histone methylation of the MALAT1 promoter, thereby upregulating MALAT1 expression and enhancing the activity of the β-catenin signaling pathway. Furthermore, Liang et al [33] identified many novel methylation-regulated differentially expressed genes involved in colon cancer tumorigenesis and progression by identifying hypermethylated downregulated genes and hypomethylated upregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Histone demethylase jumonji C domain-containing 2C (JMJD2C) is known to demonstrate regulatory potentials in the epigenetic mechanism in malignant diseases, particularly in regard to moderating the influence on the promoter activity of target genes which are strongly associated with tumor development [16]. Prior evidence has proposed that JMJD2C is highly-expressed in OS, and even confers a regulatory role in the context of OS [17].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA SLCO4A1-AS1 inhibits the interaction of b-catenin with GSKb, inhibits b-catenin phosphorylation, and improves b-catenin stability, ultimately promoting the proliferation, migration, and invasion of CRC cells (82). Wu et al (83) showed that lncRNA JMJD2C promotes CRC metastasis by enhancing the b-catenin signaling pathway and participating in the regulation of histone methylation at the MALAT1 promoter. In addition to directly participating in b-catenin signaling pathway transduction, lncRNAs can also play indirect regulatory roles in this signaling pathway.…”
Section: Lncrnas Regulate Crc Metastasis By Regulating Signaling Pathmentioning
confidence: 99%